Dental Implant Materials 2019 - Yeo, In-Sung (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Dental implant materials are advancing in the fusion of various scientific fields. Surface modification technologies for implants have been applied to titanium at the micro-level for about four decades. Now, implant surfaces are being topographically and chemically modified at both the micro- and nano-level. The modification techniques are altering other metals and ceramics, making these materials more biocompatible. Materials for abutments in dental implant systems appear to depend on implant-abutment connection structures. Biomechanical factors, such as friction and preload, influence the development of the abutment materials. Additionally, the surfaces of the abutment materials are important in the soft-tissue attachment, which is being actively investigated. As dental implants have to be functional in human bodies for a long time, numerous materials are being clinically tested as implant-supported restorations. The Special Issue, "Dental Implant Materials 2019", introduces the creative works of scientists on the current advancements in the field of materials for implant dentistry.